Price, people, location, culture and reputation: determinants of Malaysia as study destination by international hospitality and tourism undergraduates - Lee, Sanghyeop; Nguyen, Hong Ngoc; Lee, Kai Sean; Chua, Bee Lia; Han, Heesup (Taylor & Francis, 2018)
This study aims to examine why international hospitality and tourism (H&T) undergraduates (IHTUs) travel to Malaysia for higher education and what factors influence their choices. In-depth interviews were conducted with IHTUs studying in six different private higher education institutions. Thematic analysis found five noble factors: price, people, location, culture and reputation. Our findings can assist Malaysian private institutions in better meeting IHTUs’ expectations and reinforcing their loyalty to the institution. Our results can also be useful to improve the quality of the H&T educational systems in Malaysia and simultaneously facilitate the country’s greater aim of becoming a knowledge-based economy and retaining sufficient skilled labor for the H&T industry. Moreover, the results of this study can be effectively used when inventing strategies for the development of international education tourism in Malaysia.